Kazakh khans of the 15th–17th centuries in the scientific heritage of Shigabutdin Marjani - Atygayev N.A. (Золотоордынское обозрение)
Research objectives: The consideration of information about the Kazakh khans of the 15th–17th centuries, contained in the scientific heritage of Shihabutdin Marjani. Research materials: Sh. Marjani’s works, medieval written historical sources, and historical scientific literature on the history of the Kazakh Khanate of the 15th–17th centuries. Results and scientific novelty: As a result of studying the works of Shigabutdin Marjani, it was found that in his works, “Mustafad al-akhbar” and “Wafiyat al-aslaf wa tahiyat al-akhlaf,” there is little material about the Kazakh khans of the 15th–17th centuries, starting with the founders of this Juchid state, Kerey and Zhanibek to Tauke-khan, son of Zhangir-khan, the last ruler of the unified Kazakh Khanate. It is established that the main sources for his work were the studies of such historians of the previous period as A.I. Levshin, V.V. Velyaminov-Zernov, as well as famous historical works by Muslim authors of the Middle Ages, written in Persian and Turkic languages. Among these historical works, it is possible to mention “Tarikh-i Rashidi” by Mirza Muhammad Haidar Duglat, “Jami at-tavarih” by Kadir-Ali-bek (Kadirgali-bek Kosumuly), and “Shajara-yi Turk” by Abu-l-Gazi-khan. Attention is drawn to the fact that in his works, Marjani uses terminology that differs from the terminology adopted in Russian literature of that time. This is explained by the fact that he was a representative of the Muslim world and wrote his works for the Muslims. Therefore, unlike other Russian historians of the 19th century, he writes “Kyrgyz”, and uses the authentic name of the nation “Kazakh” that was accepted among Muslim nations. Marjani uses the term “Kazakhstan” to denote the possessions of Kazakh khans, something which is found in some works of Muslim authors of the Middle Ages. He also uses Turkic names (Ulu[g] yuz, Orta yuz, Kichi yuz) to denote the Kazakh yuzs. In general, the scientific works of Sh. Marjani are of interest to the historical science of Kazakhstan as they contain information on the history of the Kazakh Khanate and its rulers. The scientific novelty of the study is that in this work, for the first time, the information about the Kazakh khans of the 15th–17th centuries, which are contained in the scientific works of Marjani, are highlighted and some errors in their translations into Russian are revealed.